2010
DOI: 10.1093/jac/dkq050
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent methicillin-resistant Staphylococcus aureus bacteraemia in patients treated with vancomycin

Abstract: To minimize the risk of PMRSAB, early removal of implicated devices and evaluation for metastatic infections should be encouraged. Alternative antibiotic therapy is warranted for infections due to isolates with elevated vancomycin MICs, as well as for the high rates of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 9 publications
4
62
2
1
Order By: Relevance
“…While vancomycin remains a frequently used treatment for pneumonia caused by MRSA, clinical failures in this setting have been increasingly recognized (12,31,32). As such, additional treatment options appear necessary as MRSA isolates with reduced VAN susceptibilities (MIC, 2 g/ml) are becoming more prevalent and may contribute to poorer clinical outcomes (22,32,41). In addition to reductions in potency, the relatively low penetration (ϳ50%) of vancomycin into ELF has also been suggested as a reason for the compound's diminished clinical efficacy (6,22,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…While vancomycin remains a frequently used treatment for pneumonia caused by MRSA, clinical failures in this setting have been increasingly recognized (12,31,32). As such, additional treatment options appear necessary as MRSA isolates with reduced VAN susceptibilities (MIC, 2 g/ml) are becoming more prevalent and may contribute to poorer clinical outcomes (22,32,41). In addition to reductions in potency, the relatively low penetration (ϳ50%) of vancomycin into ELF has also been suggested as a reason for the compound's diminished clinical efficacy (6,22,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…These complicated infections in turn lead to poorer outcomes (170,171). Even in the absence of metastatic complications, persistence per se portends a worse outcome, with infection-related mortality rates being higher for patients with MRSA-B persistence (Ͼ3 days) than for nonpersistent episodes (45.2% and 9.4%, respectively; P ϭ 0.002) (323). Similar results were obtained by a larger case-controlled study, where mortality rates for persistent (Ͼ7 days) SAB were significantly higher than mortality rates for nonpersistent controls (54.8% and 31.4%, respectively; P Ͻ 0.01) (93).…”
Section: Persistent Bacteremiamentioning
confidence: 99%
“…In many of the reported studies looking at in vitro susceptibility data, MIC testing was performed retrospectively on isolates retrieved from storage, not at the time of isolation of the organism, and often this is not made explicitly clear (1,7,8,10,12,13,15,16,18,19,25,27,28,30,31,32,34,35). It has been demonstrated that certain organisms can become more susceptible when stored (3,22), and it is possible that this phenomenon, together with differing methodologies, may explain some of the conflicting results in the literature (9).…”
mentioning
confidence: 99%